If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2p + 1) = -4 Reorder the terms: 5(1 + 2p) = -4 (1 * 5 + 2p * 5) = -4 (5 + 10p) = -4 Solving 5 + 10p = -4 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 10p = -4 + -5 Combine like terms: 5 + -5 = 0 0 + 10p = -4 + -5 10p = -4 + -5 Combine like terms: -4 + -5 = -9 10p = -9 Divide each side by '10'. p = -0.9 Simplifying p = -0.9
| -39+12x=7x+26 | | -2.75-18.4j=-3.88-18.5j | | -4j-4=-2j | | 6(7-f)+f=36+f | | f(x)=20x+10 | | -18.52+9.4g=14.9g+19.98 | | 9b+7=10b | | -59+9x=53+2x | | -15.08+15.4c+14.39=0.63+19.8c | | -17.5w=5(11.1w+16.06) | | -8z=-9z-9 | | -8=-4(y-18)+-8 | | -2x-69=76-7x | | 16y-18=-16 | | -9.8p=2.8p-6.3 | | 2(x+-3)=-2 | | 4(3x+x)+7-5x=8+9(-5)(5x-6x)+23 | | X+3.8=9.1 | | -8(n+4)=7(2n+8) | | 44a=14-2a | | -4h=-16-3h | | -2(n-14)=-10 | | 20e^4t=11e^9t | | -6=2.5w-5 | | 16.3y=-2(9.8y+18.97)-18.3y | | 23+6c=95 | | 16+n+20=-17n-18 | | 2(s+1)-2=4 | | 15+b=25 | | 6(2p-2)=-24 | | 9=3(f+2) | | 3b+20=5b-12 |